2005
DOI: 10.1021/jf052098c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Odor-Active Volatiles in Champa (Campomanesia lineatifolia R. & P.)

Abstract: Volatile extracts from pulp, peels, leaves, and seeds of champa (Campomanesia lineatifolia R. and P.) were obtained by continuous liquid-liquid extraction with pentane/dichloromethane (1:1), and their chemical composition was determined by using HRGC and HRGC-MS. Differences between C. lineatifolia volatile extracts with regard to the identified compounds are presented; however, in all of them the beta-triketones were detected as major constituents (between 50 and 60% of total extract). An odor profile descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 29 publications
1
21
0
5
Order By: Relevance
“…Em testes eletroantenográficos os autores puderam detectar no extrato de goiaba, a presença de oito substâncias bioativas em antenas de machos e sete, em de fêmeas, as quais foram caracterizadas estruturalmente como: butirato de etila, (E)-3-hexenol, (Z)-3-hexenol, hexanol, hexanoato de etila, acetato de hexenila, butirato de (Z)-3-hexenila e octanoato de etila. Essas mesmas substâncias também foram observadas em extratos de frutos de araçazeiro (PINO et al, 2001) e algumas delas, tais como, butirato de etila, (Z)-3-hexenol, hexanol, hexanoato de etila, também foram detectadas em extratos de frutos de guabiroba-dafolha-finaba -Campomanesia lineatifolia (Myrtaceae) (OSORIO et al, 2006). Tabela II.…”
Section: Discussionunclassified
“…Em testes eletroantenográficos os autores puderam detectar no extrato de goiaba, a presença de oito substâncias bioativas em antenas de machos e sete, em de fêmeas, as quais foram caracterizadas estruturalmente como: butirato de etila, (E)-3-hexenol, (Z)-3-hexenol, hexanol, hexanoato de etila, acetato de hexenila, butirato de (Z)-3-hexenila e octanoato de etila. Essas mesmas substâncias também foram observadas em extratos de frutos de araçazeiro (PINO et al, 2001) e algumas delas, tais como, butirato de etila, (Z)-3-hexenol, hexanol, hexanoato de etila, também foram detectadas em extratos de frutos de guabiroba-dafolha-finaba -Campomanesia lineatifolia (Myrtaceae) (OSORIO et al, 2006). Tabela II.…”
Section: Discussionunclassified
“…Studies reporting on C. xanthocarpa (Limberger et al, 2004) and C. phaea (Adati, Ferro, 2006) leaves, both collected in the vegetative stage, showed predominance in the sesquiterpenes, while in the C. lineatifolia (Osorio et al, 2006) leaves studied during the fruit-bearing stage the major compounds were 1,8-cineol, α-pinene and β-caryophyllene.…”
Section: Characterization Of the Essential Oilsmentioning
confidence: 93%
“…Studies reported the isolation of three yellow pigments of the C. lineatifolia seeds, named champanones. Terpenes were identified in volatile extracts of pulp, peel, leaves and seeds in the same species (Bonilla et al, 2005;Osorio et al, 2006). Chemical studies of Campomanesia genus have identified quercetin, myricetin and rutin by HPLC (Schmeda-Hirschmann, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Se identificaron también volátiles como el 4-hidroxi--ionol y la -ionona, detectados con frecuencia en vino (Salinas et al, 2004;Williams et al, 1993Williams et al, , 1995 y frutas tropicales (Osorio et al, 2006;Ollé et al, 1998), son característicos por su aroma agradable, considerados como compuestos provenientes de la degradación de los carotenoides y contribuyentes importantes al aroma en frutas. De ellos, el 3-oxo--ionol tuvo una mayor concentración al pH neutro, aunque a pH ácido también fue detectado sugiriendo que puede estar enlazado a glicósidos.…”
Section: Influencia Del Ph En La Composición De Volátilesunclassified
“…De la gran diversidad de compuestos encontrados en el aroma de las frutas tropicales, los ésteres juegan un papel importante, al igual que los aldehídos, los alcoholes y compuestos de tipo terpénico principalmente oxigenados (Pino et al, 1997Pino y Quijano, 2007, Quijano y Pino, 2007Osorio et al, 2006;2011, 2011aParada et al, 2000Parada et al, , 2002Suárez y Duque, 1991;Suárez et al, 1991;Duque et al, 1993). muestra en un baño de hielo para evitar su calentamiento durante la homogenización.…”
Section: Introductionunclassified